The Importance of Riparian Vegetation for Water Quality and Tadpole Health in Agricultural Streams - Marchand, Justin (Université d'Ottawa | University of Ottawa, 2024)
Amphibians in agricultural drainage ditches may be exposed to contaminants through runoff. The goal of this study was to determine how riparian vegetation affects water quality and amphibian health metrics in drainage ditches in the South Nation River Watershed, Ontario. Cages containing northern leopard frog (Rana [Lithobates] pipiens) tadpoles were placed within nine agricultural ditches differing in their vegetation height and percentage of forest cover for 8 weeks (May-July). Physiochemical water quality measurements, contaminant concentrations and tadpole fitness-relevant metrics were assessed. Sites higher in forest cover tended to have lower specific conductance, neonicotinoids, atrazine, nitrate, and potassium concentrations. Tadpole size (snout-to-vent length, tail length, mass) was positively associated with forest cover, but all tested tadpoles were negative for Batrachochytrium dendrobatidis and Frog Virus 3, suggesting these pathogens are not present in these systems. Overall, forest cover appears to play an important role for both water quality and tadpole growth.
Keywords: Amphibians; Agriculture; Ditch; Pesticides; Nutrients; Contaminants; Pathogens